Characteristics of bystander cardiopulmonary resuscitation for paediatric out-of-hospital cardiac arrests: A national observational study from 2012 to 2014. (February 2017) - Chang, Ikwan; Kwak, Young Ho; Shin, Sang Do; Ro, Young Sun; Kim, Do Kyun
Abstract: Objectives: This study evaluated the associations between the provision of bystander cardiopulmonary resuscitation (BCPR) and both the relationship of bystanders with paediatric out-of-hospital cardiac arrest (OHCA) victims and the community educational level. Methods: This observational study was conducted using the Korean national OHCA registry of paediatric OHCAs (<19 years old) between 2012 and 2014. The main factor was the relationship between the bystander and the OHCA victim. The primary endpoint was the provision of BCPR. The association between BCPR provision and community educational level was also examined. Multivariable logistic regression and interaction analyses were performed to determine whether community educational level affected BCPR provision. Results: Among the 1477 enrolled patients, 725 (49.1%) received BCPR. Family members provided BCPR in 458 (57.4%) cases. The adjusted odds ratios and corresponding 95% confidence intervals (AORs, 95% CIs) for the provision of BCPR by family members or first responders compared with strangers were 1.75 (1.31–2.34) and 8.90 (5.00–15.84). The AORs for BCPR provision in communities with the middle and lowest educational levels compared with the highest were 0.70 (0.53–0.92) and 1.11 (0.79–1.55). The interaction analysis showed that the AORs of family members or first responders providing BCPR compared with strangers were 1.32 (0.79–2.19) and 5.90 (1.98–17.63), 1.98 (1.31–2.98) and 10.88 (4.20–28.16), and 1.87 (1.18–2.96) and 9.89 (3.88–25.21) in communities with the lowest, middle and highest educational levels, respectively. Conclusion: In paediatric OHCA cases, family members were more likely than strangers to perform BCPR except in communities with the lowest educational level.